Mechanistic integration of thermodynamic quality during transient air blast freezing of export-grade shrimp: Integrasi mekanistik termodinamika-kualitas selama air blast freezing transien pada udang kelas ekspor - Nugroho, Faizin Adi; Krisnafi, Yaser; Khikmawati, Liya Tri; Lailatussifa, RR. Radipta; Astiana, Ika; Pratiwi, Citra Zaskia (Jurnal Pengolahan Hasil Perikanan Indonesia, 2026)
Shrimp quality is highly sensitive to freezing stability during early post-harvest handling. Although air blast freezers (ABF) are widely applied in industrial processing, the quantitative linkage between transient thermodynamic degradation and early microstructural deterioration remains insufficiently resolved. This study aims to investigate the mechanistic relationship between early-stage ABF performance decay and time-resolved shrimp quality changes during the first 6 h of freezing. An integrated experimental approach was conducted by combining in-situ measurements of airflow velocity, air-side temperature differential (ΔT), evaporator frosting mass, cooling capacity (Q), and actual coefficient of performance (COP) with laboratory analyses of ice crystal size, water-holding capacity (WHC), drip loss, texture, pH, melanosis, and TVB-N. The results demonstrate a progressive frosting accumulation (0.09-1.50 kg) that reduced airflow (4.38-2.62 m s⁻¹), suppressed cooling capacity (28.99-20.98 kW), and deteriorated COP (3.51-2.33). Frosting mass explained up to 97-98% of COP and Q variance. Sequential regression analysis confirmed a strong mechanistic pathway: COP decline significantly enlarged ice crystals (R² = 0.97), which reduced WHC (R² = 0.96) and increased drip loss (R² = 0.98). These findings indicate that transient thermodynamic instability, rather than steady-state temperature compliance alone, governs early structural degradation. The study repositions COP as a predictive upstream control parameter linking machine performance to product integrity and provides a performance-oriented framework for HACCP-integrated monitoring and early operational optimization in industrial shrimp freezing systems.